2017
DOI: 10.1159/000458418
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Levels of Vitamin D are Associated with Progression of Subclinical Atherosclerotic Vascular Disease in Peritoneal Dialysis Patients: A Prospective, Multicenter Study

Abstract: Background: The prevalence of subclinical atherosclerosis and the main predictors of progression of this condition in patients undergoing peritoneal dialysis (PD) have been insufficiently investigated. Objectives and Method: Following a prospective, multicenter, observational design, we studied 237 patients who were treated with PD for ≥3 months, without any clinical background of cardiovascular (CV) disease. Our objectives were the following: (1) to investigate the prevalence of subclinical atherosclerosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…By reviewing the full articles, 51 articles were further rejected for the following reasons: (1) data were unavailable to calculate the OR/hazard ratio (eg, quantitative variables); (2) no outcome data of interest were included; and (3) the study was a basic research/review article or not related. Finally, 11 studies were eligible for inclusion in our analysis …”
Section: Resultsmentioning
confidence: 99%
“…By reviewing the full articles, 51 articles were further rejected for the following reasons: (1) data were unavailable to calculate the OR/hazard ratio (eg, quantitative variables); (2) no outcome data of interest were included; and (3) the study was a basic research/review article or not related. Finally, 11 studies were eligible for inclusion in our analysis …”
Section: Resultsmentioning
confidence: 99%
“…In a subpopulation of the NEFRONA study involving 1553 participants with different stages of chronic kidney disease, cIMT was associated with new plaque progression in dialysis patients . In another subpopulation of the NEFRONA study including 237 patients undergoing peritoneal dialysis, individuals in the median and highest third of baseline cIMT had a higher risk for progression of atherosclerotic disease compared to individuals in the lowest third of baseline cIMT …”
Section: Discussionmentioning
confidence: 99%
“…45 In another subpopulation of the NEFRONA study including 237 patients undergoing peritoneal dialysis, individuals in the median and highest third of baseline cIMT had a higher risk for progression of atherosclerotic disease compared to individuals in the lowest third of baseline cIMT. 46 In order to predict the genesis of carotid plaques, it is important to study initiation and progression of atherosclerosis. The mechanisms behind the development of atherosclerosis consist of many different facets including inflammation, endothelial dysfunction, oxidation, lipid accumulation, proliferation and migration of vascular smooth muscle cells, which lead to manifestation of atherosclerotic plaques in the vessel walls that can further cause thrombosis and stenosis in human arteries.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also recognized that the stroke risk profiles of CAPD patients are slightly different from those of the general population because of the loss of residual renal function, which may contribute to disorders of mineral and bone metabolism, volume overload, irrepressible hypertension, electronic disorder, and treatment with glucose-based dialysis solutions. Commonly, increased serum parathyroid hormone (PTH) levels and vitamin D insufficiency are universal among CAPD patients and are mostly attributed to chronic kidney disease-mineral and bone disorder (CKD-MBD) [8][9][10]. Accumulating evidence has indicated that vitamin D deficiency or insufficiency significantly increased cardiovascular disease (CVD) events among the general or dialysis population [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%